2019
DOI: 10.1080/1059924x.2019.1592049
|View full text |Cite
|
Sign up to set email alerts
|

Conventional and Complementary Therapy Use among Mexican Farmworkers in North Carolina: Applying the I-CAM-Q

Abstract: Objectives: This analysis documents the use of conventional health care providers, traditional healers, and complementary therapies by Mexican farmworkers; identifies the purposes and perceived helpfulness of these modalities; and delineates variation in the use of traditional healers and complementary therapies. Methods: Two-hundred Mexican farmworkers in North Carolina completed interviews May-September, 2017. The International Complementary and Alternative Medicine Questionnaire (I-CAM-Q) elicited use of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 52 publications
(72 reference statements)
1
11
0
Order By: Relevance
“…Natural medicine is a common practice in many Latino cultures, used to protect individuals and their families. Many Latinos use complementary and alternative medicine due to a lack of access to health care in the United States (Nguyen et al 2014;Arcury et al 2019). It is unsurprising that participants in this study mentioned the use of natural remedies: Lee et al (2010) demonstrated that recent immigrant populations in the US retain alternative medical practices more so than stable, established populations of immigrants.…”
Section: Discussionmentioning
confidence: 87%
“…Natural medicine is a common practice in many Latino cultures, used to protect individuals and their families. Many Latinos use complementary and alternative medicine due to a lack of access to health care in the United States (Nguyen et al 2014;Arcury et al 2019). It is unsurprising that participants in this study mentioned the use of natural remedies: Lee et al (2010) demonstrated that recent immigrant populations in the US retain alternative medical practices more so than stable, established populations of immigrants.…”
Section: Discussionmentioning
confidence: 87%
“…This study has important implications for the development of patient-centered, culturally sensitive health care that integrates an awareness and respect for medical pluralism among health care providers. Researchers have explored the concept of medical pluralism among other immigrant groups resettled in Europe and North America, including Pakistani migrants (Nasiruddin, 2018), Vietnamese refugees (Nguyen et al, 2016), and Mexican farmworkers and immigrants (Arcury et al, 2019; Sandberg et al, 2018). Similar to our findings, these studies suggest widespread use of traditional medicine and complex pathways to care and decision-making processes around when to use formal or informal care.…”
Section: Discussionmentioning
confidence: 99%
“…From 2012 to present, the questionnaire has been translated and adapted to many different countries and languages [ 15 20 ]. The I-CAM-Q instrument has been applied worldwide such as in France [ 15 ], Germany [ 20 ], Iran [ 16 ], Saudi Arabia [ 21 ], US [ 22 , 23 ], Argentina [ 24 ], Japan [ 25 , 26 ], Taiwan [ 17 ], Korea [ 18 ], Cambodia [ 27 ] and Australia [ 28 ]. In 2012 Eardley et al published a paper with the aim to “generate preliminary evidence concerning the face validity, acceptability and basic characteristics of the I-CAM-Q across different populations”.…”
Section: Introductionmentioning
confidence: 99%